1986
DOI: 10.1073/pnas.83.15.5517
|View full text |Cite
|
Sign up to set email alerts
|

Inducible adhesion of mesenchymal cells to elastic fibers: elastonectin.

Abstract: The addition of highly purified elastic fibers to confluent human skin fibroblast or porcine aorta smooth muscle cell cultures resulted in a time-dependent, strong adhesion of the fibrils to the cell surface. The kinetics of adhesion was studied by video/time-lapse cinematography. After a 0.5-1 hr lag period, adhesion progressed to a maximum amount in 3-6 hr in the described conditions. Adhesion is strongly accelerated by the prior addition of soluble elastin peptides (K-elastin) to the cultures. Cycloheximid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
35
0

Year Published

1990
1990
2011
2011

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(39 citation statements)
references
References 18 publications
(17 reference statements)
1
35
0
Order By: Relevance
“…We have reported that tropoelastin downregulates the induction of calcification via the elastin receptor (manuscript in submission), although the pathway of the inhibitory reaction by TE on calcification presents several candidate reactions such as the activation of signal transduction via the elastin receptor (33) and the binding of calcium by tropoelastin molecule (6,7). Moreover, it has been reported that TE has a variety of biological effects which are mediated by the elastin receptor, chemotactic cell migration, modulation of ion flux, adhesion of cells to elastin fibers, tumor cellmatrix interaction, elastase synthesis and release, free radical production, endothelium and nitric oxide-mediated vasorelaxation, chaperon for elastogenesis, lymphocyte proliferation, apoptotic cell death (34)(35)(36)(37)(38) as well as properties as a major elastic fiber component. In this study, we revealed a new candidate function of the TE molecule.…”
Section: Discussionmentioning
confidence: 99%
“…We have reported that tropoelastin downregulates the induction of calcification via the elastin receptor (manuscript in submission), although the pathway of the inhibitory reaction by TE on calcification presents several candidate reactions such as the activation of signal transduction via the elastin receptor (33) and the binding of calcium by tropoelastin molecule (6,7). Moreover, it has been reported that TE has a variety of biological effects which are mediated by the elastin receptor, chemotactic cell migration, modulation of ion flux, adhesion of cells to elastin fibers, tumor cellmatrix interaction, elastase synthesis and release, free radical production, endothelium and nitric oxide-mediated vasorelaxation, chaperon for elastogenesis, lymphocyte proliferation, apoptotic cell death (34)(35)(36)(37)(38) as well as properties as a major elastic fiber component. In this study, we revealed a new candidate function of the TE molecule.…”
Section: Discussionmentioning
confidence: 99%
“…Elastin and fibrillin have been found to be present during the embryonic stages of heart development (Rosenquist et al, 1988;Gallagher et al, 1993). In addition, since elastin has been found to interact with neighboring cells by means of specific receptors (Hornebeck et al, 1986;Hinek et al, 1988), it may provide a structural link required for the generation of mechanical forces which are important during the morphogenesis of the heart.…”
Section: Introductionmentioning
confidence: 99%
“…41 Hornebeck et al 41 propose that the loss of the cell-elastin interaction leads to the modulation of the contractile to the synthetic phenotype of SMCs characteristic of the atherosclerotic vessel. To what degree this and other extracellular matrix components, such as proteoglycans organized in the type I collagen lattice, 742 may regulate biosynthetic activity by direct interaction or by influ- encing the effect of various growth factors 4344 remains to be elucidated.…”
Section: Discussionmentioning
confidence: 99%